Internet of Things Education Teaching and Learning Centre Harapan Bunda School Jakarta - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Agus Dendi Rochendi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The DC (Domestic Cooperation) CS (Community Service) program proposes IoT (Internet of Things) training, which aims to educate trainees to get to know the latest internet-based technology supported by accompanying instructors in their fields of expertise based on the approach of published research results, especially in electrical engineering, and conduct educational counseling on variations and models to support IoT. The training participants were students at TLC (Teaching and Learning Centre) in Harapan Bunda, Jakarta. Initial observations showed the participants' interest in IoT technology, so the contribution is support for improving the quality of skilled labor to be aligned with industry needs. This CS method includes showing the results of scientific publications, providing IoT material, simple coding training, and simple practice. This CS activity is expected to make the participants able to understand the concept of IoT and practice the application of IoT in everyday life. The measurement of the percentage of training success is a satisfaction survey questionnaire. The CS activity resulted in a satisfaction percentage of 93%, and it was hoped that the CS program could be carried out regularly and be of benefit to students who need additional skills as a future provision.